2022
DOI: 10.3233/jad-220261
|View full text |Cite
|
Sign up to set email alerts
|

B Lymphocytes in Alzheimer’s Disease—A Comprehensive Review

Abstract: Alzheimer’s disease (AD) represents the most common type of neurodegenerative dementia and is characterized by extracellular amyloid-β (Aβ) deposition, pathologic intracellular tau protein tangles, and neuronal loss. Increasing evidence has been accumulating over the past years, supporting a pivotal role of inflammation in the pathogenesis of AD. Microglia, monocytes, astrocytes, and neurons have been shown to play a major role in AD-associated inflammation. However recent studies showed that the role of both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 225 publications
0
7
0
Order By: Relevance
“…Once activated by their cognate pathogenic signal, B cell subset functions within the broader immune response include (1) antigen presentation via major histocompatibility complexes (MHC) to effector immune cells, namely CD4 + or CD8 + T cells, (2) antibody production, and (3) pro- or anti-inflammatory cytokine secretion. These functions coordinate and potentially amplify, restrain, or resolve the broader immune response ( Engler-Chiurazzi et al, 2020 ), and also serve as the foundation for immune memory to a given immunogen ( Plantone et al, 2022 ). IL, Interleukin; TCR, T Cell Receptor; TGF, Transforming Growth Factor; TNF, Tumor Necrosis Factor.…”
Section: Brief Background Of B Cell Development and Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Once activated by their cognate pathogenic signal, B cell subset functions within the broader immune response include (1) antigen presentation via major histocompatibility complexes (MHC) to effector immune cells, namely CD4 + or CD8 + T cells, (2) antibody production, and (3) pro- or anti-inflammatory cytokine secretion. These functions coordinate and potentially amplify, restrain, or resolve the broader immune response ( Engler-Chiurazzi et al, 2020 ), and also serve as the foundation for immune memory to a given immunogen ( Plantone et al, 2022 ). IL, Interleukin; TCR, T Cell Receptor; TGF, Transforming Growth Factor; TNF, Tumor Necrosis Factor.…”
Section: Brief Background Of B Cell Development and Activationmentioning
confidence: 99%
“…The next question to be answered is what might B cells be doing in the stressed CNS? The answer may be condition specific as B cells appear to be pathogenic drivers in autoimmunity and Alzheimer’s-like dementia whereas they may be neurorestorative in acute brain or spinal cord injury ( Engler-Chiurazzi et al, 2020 ; Plantone et al, 2022 ; Maheshwari et al, 2023 ; Malone et al, 2023 ).…”
Section: Mechanisms By Which B Cells Migrate To Access and Remain At ...mentioning
confidence: 99%
See 1 more Smart Citation
“…While the role of B cells is typically thought to be advantageous, recent research on AD animal models has shown that a genetic loss of B cells alone or their depletion at the onset of AD may be beneficial. This highlights that B cells may have a notable detrimental impact on AD progression [ 353 ].…”
Section: The Role Of Immune System In Admentioning
confidence: 99%
“…There is inadequate evidence and inconsistent data in the literature on the function of B lymphocytes, plasma cells, and antibodies in neuroinflammation and ND [54,55], and their contribution in AD pathogenesis needs further investigation. The diverse and obscure points of neuroinflammation and ND [56] could also be clarified.…”
Section: Clonotypic Immune Cells In Neuroinflammation and Ndmentioning
confidence: 99%